HUBUNGAN KARAKTERISTIK DEMOGRAFI DENGAN PENGETAHUAN MASYARAKAT TENTANG HIV (Human Immunodeficiency Virus)/ DI RW 02 KELURAHAN PINANG RANTI JAKARTA-TIMUR - Ida Diana Sari; Nina Rustiana; Aulia Eka Damayanti (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Human Immunodeficiency Virus (HIV) is a virus that attacks and weakens the human body's defense system, making the body susceptible to various diseases. By the end of 2022, 85.6 million people will be infected with the HIV virus and around 40.4 million people will die from HIV. The global prevalence of people living with HIV is 39.0 million. According to the Executive Report on the Development of HIV/AIDS and Sexually Transmitted Diseases (PIMS) for the first quarter of 2023, there were 5 provinces that reported the highest HIV cases in Indonesia DKI Jakarta 82,033 cases, East Java 79,026 cases, West Java 62,315 cases, Central Java 50,689 cases, and Papua 44,086 cases. The purpose of this study was to determine the level of community knowledge about HIV / AIDS in RW 02 Pinang Ranti Village in the March-April 2024 period. The method in this study uses quantitative descriptive method. There were 342 samples in this study, which were obtained using the Propotional Random Sampling technique. The results of community knowledge in RW 02 Pinang Ranti Village, East Jakarta, which are in the good category are 114 respondents (33,33%), who have sufficient knowledge are 165 respondents (48.25%), and who have poor knowledge are 63 respondents (18,42%). It can be concluded that the knowledge of the community in RW 02 Kelurahan Pinang Ranti East Jakarta is in the moderate category (48,25%). Based on statistical calculations using the Spearman rho test, there is no relationship between the demographic characteristic of gender and public health knowledge about HIV/AIDS in RW 02 Pinang Ranti Village for the period of March-April 2024.